Early Neurological Assessment and Long-Term Neuromotor Outcomes in Late Preterm Infants: A Critical Review - Domenico M. Romeo; Martina Ricci; Maria Picilli; Benedetta Foti; Giorgia Cordaro; Eugenio Mercuri (Medicina, 2020)
Background and Objectives: Late preterm (LP) infants (born between 34 and 36 weeks of gestational age) are considered at higher risk of neonatal morbidities, mortality, and neurological impairments than full-term born infants (FT). The aim of this study was to provide a critical review of the literature outlining the different aspects of neurological function reported both in the neonatal period and in the follow up of late preterm infants. Materials and Methods: A comprehensive search of the MEDLINE, Embase, PsycINFO, and CINAHL electronic databases was made, using the following search terms: ‘Late preterm infants’, ‘Near term infants’, ‘neurological assessment’, ‘neurological outcome’, ‘neuromotor outcome’, cerebral palsy’, ‘CP’, ‘motor impairment’, including all the studies reporting clinical neurological assessment of LP (including both neonatal period and subsequent ages). Results: A total of 35 articles, comprising 301,495 children, were included as fulfilling the inclusion criteria: ten reported neonatal neurological findings, seven reported data about the first two years after birth, eighteen reported data about incidence of CP and motor disorder during the infancy. Results showed a more immature neurological profile, explored with structured neurological assessments, in LP infants compared with FT infants. The LP population also had a higher risk of developing cerebral palsy, motor delay, and coordination disorder. Conclusion: LP had a higher risk of neurological impairments than FT infants, due to a brain immaturity and an increased vulnerability to injury, as the last weeks of gestational age are crucial for the development of the brain.